Standard handbook of machine design - Shigley, Joseph Edward; Mischke, Charles R. (McGraw-Hill, 1986)
This long-needed handbook is the first to cover the entire fields of machine design in a single volume. It emphasizes solutions to practical problems that arise on the job and includes computer-aided design methods and other sophisticated machine computational techniques.